Veiksmažodžio refleksyviojo posesyvumo raiška lietuvių senuosiuose raštuose - Maskuliūnas, Bronius (Baltistica, 2004)
THE EXPRESSION OF VERBAL REFLEXIVE POSSESSIVENESS IN THE OLD LITHUANIAN WRITINGSThe usage of reflexive verbs to denote an action performed by the subject for his/her own sake is more appropriate, although the same meaning may be expressed by non-reflexive verbs as well. For this reason the verbal constructions under discussion are divided into two groups.The number of the constructions with reflexive verbs in the old Lithuanian writings is comparatively limited. They can be divided into the constructions with reflexive verbs with a direct meaning and into the constructions with reflexive verbs with a non-direct meaning. In the first case the action is completely within the sphere of the subject whereas in the second case the reflexive affix shows extra relations between the action and the subject.The possessive reflexive constructions with non-reflexive verbs are far more numerous and varied in the old writings. The constructions of this group are attributed to that type of verbal constructions the main meaning of which is possessiveness. Reflexiveness in this case is secondary matter. The elimination of the explicit reflexive attribute does not change the meaning of the statement, i.e. reflexiveness of the sentence may be perceived implicitly. Such constructions may be divided into several minor sub-groups.Constructions with the dative case of the reflexive pronoun sau added to the verb to stress the interest of the subject basically function in the same way as the reflexive particle. The constructions under discussion are mainly used in the sphere of the third person, the dative case sau most often is used with the verbs (imti, daryti, rinkti) denoting recipience rather than possession. The constructions with the adessive case of the reflexive pronoun are also within the third person sphere. The adessive of the reflexive pronoun is mainly used with the verb turėti. The adessive generally corresponds to the modern Lithuanian inessive in constructions of this type. Commonly the verbs (or their derivatives) imti, nešti, vesti, turėti are used in constructions with the instrumental case of the reflexive pronoun savim(i). Constructions of this type are synonymous with the combinations with reflexive verbs.In special cases reflexive possessiveness may be expressed by non-reflexive verbs where only the context reveals that the action has been performed for the sake of the subject. Such sentences are clearly ambiguous and a wider context is necessary to understand their real meaning. Reflexive verbs are more appropriate for the constructions under discussion. Therefore, they are more widely used in modern Lithuanian. In general the usage of the verb to denote reflexive possessiveness is narrower than the usage of the pronoun in the old writings, whereas in the modem Lithuanian it is the reflexive verbs which prevail to express reflexive possessiveness. The function of reflexive verbs to denote actions performed for the sake of the subject is comparatively new. The analysis of the constructions in the old writings and their comparison with the equivalents in modern Lithuanian lead to the conclusion that the expression of reflexive possessiveness in the Lithuanian language is in the process of evolving from analytical to synthetic constructions.
Keywords: senieji raštai; posesyvumas; veiksmažodis; lietuvių kalba